L’approche Par Competences Et La Question De La Montee Des Inegalites Scolaires En Cote d’Ivoire. Analyse Des Pratiques Des Pratiques Enseignantes En Classe Sur Le Profil De Sortie Des Eleves Du Premier Cycle Du Secondaire En Cote d’Ivoire. - Nguessan Kouamé (European Scientific Journal, ESJ, 2018)
Considered as a tool to understand the academic achievements, the orientations, the access to the different sectors, the obtaining of diplomas, etc., the concept of school inequalities is the prism by which we evaluate the school, its operation and its ability to fulfill the explicit missions that are its own. We specifically question the impact of classroom teaching practices on the exit profile of students in the "Science" field and consequently on the graduation rate of students in the secondary education of the first cycle, which is a necessary condition of access. to have a job; and therefore a factor of school inequalities. This study aims to point out certain difficulties and obstacles observed in reading the didactic intentions of the educational programs by the teachers. Surveys based on observation grids on the one hand, audio and video recordings, and interviews on the other, were conducted on three types of teachers (competent, efficient, and expert) by discipline in each of the three disciplines of the field "Science" in the fourth year of junior high school. The results show that these teachers, despite their certain skills, have many shortcomings in mastering the components of the different knowledge required for effective teaching / learning. As a result, some teaching strategies have to be adjusted to fill the knowledge gap among the latter. Given these shortcomings, continuous teacher training that takes into account all disciplinary, curricular, didactic and pedagogical aspects is necessary to give the learner the desire to follow, to pursue studies, develop more skills, and consequently reduce school inequalities.